Excessive Sleep and Lack of Sleep Are Associated With Slips and Falls in the Adult Korean Population: A Population-Based Cross-Sectional Study. Issue 4 (January 2016) - Kim, So Young; Kim, Sung-Gyun; Sim, Songyong; Park, Bumjung; Choi, Hyo Geun
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Few studies have evaluated the impacts of excessive sleep duration on falls. This study investigated the associations between sleep duration and falls among Korean adults in a wide range of age groups while adjusting for numerous confounding factors. Data collected from study participants ranging in age from 19 to 109 years old were analyzed from the 2013 Korean Community Health Survey (KCHS). Sleep duration was divided into 5 groups: ≤5, 6, 7, 8, and ≥9 hours per day. The relations between sleep duration and falls (≥1 time or ≥2 times per year) were analyzed using simple and multiple logistic regression analyses with complex sampling. Age, sex, days of vigorous or moderate physical activity, income, education, alcohol use, smoking, stress, obesity, hypertension, diabetes mellitus, hyperlipidemia, stroke, angina or myocardial infarction, arthritis, and asthma were controlled for as confounding factors. Associations between sleep duration and falls were analyzed in 19 to 40, 41 to 60, and 61+ year age groups. Furthermore, the relations between sleep duration and indoor versus outdoor falls were analyzed. Both ≤6 and ≥8 hours of sleep per day were significantly associated with an increased incidence of falls (≥1 time and ≥2 times per year) in the overall adult population ( P  < 0.001 in both instances). In a subgroup analysis, sleep durations of ≤5 and ≥9 hours were significantly associated with an increased incidence of falls (≥1 time a year) in each age group. Six hours of sleep was not significantly associated with falls (≥2 times per year) in the 61+ year age group, and 8 and 9 hours of sleep were not significantly associated with falls (≥2 times a year) in the 19 to 40 year age group. This study demonstrated that long as well as short sleep durations are associated with an increased incidence of falls. However, these relations were not evident in elderly populations with short sleep durations or in young adults with long sleep durations.